Avaliação do treinamento das brigadas de emergência na região de Medianeira: estudo de caso - Welter, Amauri (2012)
The effective norms establish trainings for the brigades of emergency on industries; however the results are not satisfactory, forming people without capacity to perform quality work. The brigades of emergency plus provide security to members of the constructions are a much-needed contribuition to the fire department, helping in the prevention and containment of possible claims, it is up this brigade properly receive the necessary instructions to provide an effective work. The disposition of time for these people receive adequate training is essential, because they are always working to better the institution itself.